A case of Budd-Chiari syndrome with Behcet's disease and oral contraceptive usage - BALTACIOĞLU, FEYYAZ; DURMUŞOĞLU, LÜTFİYE; DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2007)
We present a case of Budd-Chiari syndrome (BCS) having two risk factors, Behcet's disease (BD) and oral contraceptive (OC) usage. A 33-year-old woman with BD was admitted to the Emergency Unit with nausea, vomiting, abdominal pain, abdominal distention, and confusion started 12 days ago before admission. Since the patient was in a shock state, she was taken to the Intensive Care Unit (ICU) with the suspicion of abdomen-originated sepsis. Abdominal ultrasound showed massive hepatosplenomegaly and moderate ascites. Abdominal MRI revealed an inferior vena cava (IVC) obstruction starting above the renal veins and diffuse thrombosis of the right and medial hepatic veins. An extensive thrombosis of the IVC and the hepatic veins (BCS) which led to shock was diagnosed. In addition to BD, the unnotified OC usage for a year by the patient without her doctor's knowledge was recognized as possible precipitating factor of BCS. Pulse methylprenisolone was started for three consecutive days to treat active BD-induced vasculitis. IVC digital subtraction angiography (DSA) showed occlusion of the IVC below the hepatic veins with extensive collateral circulation originating at the occlusion level suggesting that obliteration had a subacute or chronic course. Since intralesional thrombolytic therapy failed, the patient was transferred to a liver transplantation center. While waiting for an appropriate donor, the patient died due to hepatic failure. Since BCS is mortal and deemed multi-factorial, every patient with a thrombotic risk factor such as BD should be questioned for other possible causes of thrombosis.
Keywords: acute hepatic failure; vasculitis; venous thrombosis; Behcet's disease; HEPATIC VEIN-THROMBOSIS; V-LEIDEN MUTATION; INVOLVEMENT; RISK